Unilateral absence of the left pulmonary artery with patent ductus arteriosus and interrupted inferior vena cava - Burçak Kılıçkıran Avcı; Bilgehan Karadağ; Hasan Tüzün; Zeki Öngen (KARE Publishing, 2014)
Unilateral absence of the pulmonary artery and interrupted inferior vena cava are rare congenital disorders. The clinical presentation is variable, and many patients can be asymptomatic for many years and even throughout their lives. We report the case of a 44- year-old female patient with a history of hemoptysis. She was referred to our clinic with a diagnosis of pulmonary artery agenesis. Computed tomography revealed absence of the left main pulmonary artery and long-tract patent ductus arteriosus (PDA). Blood supply to the left lung was provided by major aortopulmonary collateral arteries (MAPCAs). Right heart catheterization through the right femoral vein was problematic, as the catheter could not be negotiated from the inferior vena cava to the right atrium. We revealed the interrupted inferior vena cava, which continued as a dilated azygos vein to the superior vena cava. The magnitude of the shunt flow from the PDA was too small, and the calculated shunt fraction was not significant. Hemoptysis was possibly due to MAPCAs. However, as the patient had no active bleeding when she was referred, the exact source of the hemoptysis could not be identified.